A novel viscoelastic-based ferrofluid for continuous sheathless microfluidic separation of nonmagnetic microparticles. Issue 20 (26th September 2016) - Zhang, Jun; Yan, Sheng; Yuan, Dan; Zhao, Qianbin; Tan, Say Hwa; Nguyen, Nam-Trung; Li, Weihua
Abstract : We proposed and developed a novel viscoelastic ferrofluid, and demonstrated its superior advantages for continuous sheathless separation of nonmagnetic particles. Abstract : Separation of microparticles has found broad applications in biomedicine, industry and clinical diagnosis. In a conventional aqueous ferrofluid, separation of microparticles usually employs a sheath flow or two offset magnets to confine particle streams for downstream particle sorting. This complicates the fluid control, device fabrication, and dilutes the particle sample. In this work, we propose and develop a novel viscoelastic ferrofluid by replacing the Newtonian base medium of the conventional ferrofluid with non-Newtonian poly(ethylene oxide) (PEO) aqueous solution. The properties of both viscoelastic 3D focusing and negative magnetophoresis of the viscoelastic ferrofluid were verified and investigated. By employing the both properties in a serial manner, continuous and sheathless separation of nonmagnetic particles based on particle size has been demonstrated. This novel viscoelastic ferrofluid is expected to bring more flexibility and versatility to the design and functionality in microfluidic devices.